A Microbiological Study on Clinical Isolates of Coagulase-Negative Staphylococci (CoNS) from Sulaimaniyah Hospitals - AL-Janabi1, Fadia Farouk; Arif, Huner Hiwa; Jalal, Paywast Jamal (Sulaimani Journal for Pure and Applied Sciences, 2022)
The purpose of this study was to identify and isolate different coagulase.negative staphylococci (CoNS) species associated with clinical samples with their virulence factors. For this purpose, 355 clinical samples were taken from various Hospitals in Sulaimaniyah city. Different species of CoNS were identified by using (blood, MacConkey, Mannitol salt) agars, biochemical tests, and VITEK® 2 compact system. The phenotypic characterization of hemolysin was based on the hemolysis pattern of CoNS on sheep blood agar. Moreover, the biofilm detection in CoNS was performed by using a microtiter plate (MTP). The various biofilm and virulence genes were detected using specific primers to detect mecA, hla, hlb, hld, hlg and the icaAD, fnbA, and bap genes, respectively. The number of MR-CoNS and MS-CoNS were 31 (96.8%) and 1 (3.1%), respectively, out of 32 isolates. The availability of the mecA gene, responsible for the resistance of CoNS to methicillin, was found in (100%) of CoNS species related to clinical samples. Interestingly, the hemolysin genes were detected on the plasmids instead of the chromosomal DNA, and these results indicated that the CoNS could be the primary cause of nosocomial infection.
Keywords: Coagulase-negative staphylococci (CoNS); Hemolysin genes; Microtiter plate (MTP; Biofilm gene